Research on adults with subthreshold depression after aerobic exercise: a resting-state fMRI study based on regional homogeneity (ReHo) - Shen, Wenbin; Wang, Xiaoxiao; Li, Qin; Ding, Qingguo; Zhang, Hongqiang; Qian, Zheng; Sun, Zhixin; Chen, Xingyu; Zhang, Jun; Zhao, Mengqi; Huang, Lina; Xing, Wei (Frontiers in Neuroscience, 2024)
Objective: Subthreshold depression(StD)/subsyndromal depression is a threatening precursor to depression. Aerobic exercise is a promising self-supportive adjunctive intervention and an effective measure for StD. Our study utilizes regional homogeneity (ReHo) to investigate the impact of aerobic exercise on resting-state brain function.Methods: 78 subjects aged between 18 and 48 years (StD group, n=44; healthy control (HC) group, n=34) engaged in moderate-intensity aerobic exercise 3-4 times per week for 8 weeks. Resting-state brain function and structural images were acquired before and after the exercise intervention. The ReHo method was employed to analyze abnormal changes in regional brain function, and correlation analysis was conducted with the Patient Health Questionnaire-9 (PHQ-9) and Self-Rating Anxiety Scale (SAS) scale score. Results: The principal observation reveals synchronal abnormalities in the right anterior cingulate gyrus of the brain in StDs compared to HCs at baseline, with these differences dissipating after the implementation of aerobic exercise. In the StD group, after completing the aerobic exercise program showed a difference in the right middle cingulate gyrus. The left supplementary motor area (SMA) was changed in the HC group. Conclusion: Neural synchronization disparities are evident between HC and StD subjects, and the implementation of aerobic exercise intervention can effectively improve these distinctions, leading to a significant reduction in depressive symptoms among StD subjects. Inhibition of the anterior cingulate gyrus may be the main mechanism of StD symptoms and the effects of aerobic exercise may be related to the modulation of emotional reflex neural synchronization. The discovery of these fMRI evidence findings may offer novel strategies for detecting and intervening early in cases of StD.